Analisis Penerapan Tax Review Pada Perlakuan Perpajakan Perusahaan: (Studi Kasus di PT. XYZ) - Ni Luh Gede Ayu Sujaniari; I Wayan Sudiana; I Wayan Budi Satriya (UNHI Press, 2026)
A tax review involves examining a company's entire tax obligations and the execution of fulfilling those obligations, including calculation, payment, settlement, and reporting, in order to evaluate tax compliance. This study was carried out at PT. XYZ, a baby shop retail company located on Jl. Kebo Iwa, Denpasar. The aim of this research is to determine whether PT. XYZ’s 2023 income tax period, including its calculation, withholding, and payment, complies with applicable tax laws and regulations. This study employs a qualitative approach with a descriptive method. The descriptive method is used to present data as it actually occurs without inserting personal opinions or generalized conclusions, with the goal of providing a clear data analysis. Data were collected through observation, interviews, and documentation techniques. The findings reveal that PT. XYZ has submitted its tax returns (SPT) on time regarding its tax deposit and reporting obligations. However, the accuracy of tax calculations still requires improvement, which should be accompanied by enhanced understanding of tax review procedures to ensure proper fulfillment of tax obligations.